CARDIAC MAGNETIC RESONANCE IMAGING IN THE DIAGNOSIS OF ACUTE MYOCARDITIS: A CLINICAL CASE AND A REVIEW OF LITERATURE - O. M. Larina; E. A. Mershina; V. E. Sinitsyn; D. A. Andreev (Вестник рентгенологии и радиологии)
The clinical manifestations of myocarditis are extremely variable and it may commonly manifest as acute myocardial infarction. The diagnosis of acute myocarditis is frequently empiric and substantiated by the clinical picture of the disease, ECG changes, elevated enzyme levels, and the lack of any data on coronary heart disease. Until recently, endomyocardial biopsy has been considered to be the most accurate diagnostic method. However, endomyocardial biopsy has a low sensitivity and is associated with the high risk of complications.This paper describes a clinical case of a patient with cardialgias occurring after acute respiratory viral disease, with ST segment elevation, and higher levels of cardiospecific enzymes. The diagnosis of myocarditis was verified by contrast-enhanced cardiac magnetic resonance imaging.